2021
DOI: 10.1002/mcf2.10143
|View full text |Cite
|
Sign up to set email alerts
|

Penaeid Shrimp in Chesapeake Bay: Population Growth and Black Gill Disease Syndrome

Abstract: Since 1991, the number of penaeid shrimp occurring in Virginia waters of Chesapeake Bay has steadily increased, prompting an interest in developing a fishery. Although development of a shrimp fishery in the Chesapeake Bay region could bring economic benefits, the fishery may be hampered by the presence of a disease syndrome known as shrimp black gill (sBG). The objectives of our study were to (1) describe the spatial distribution and abundance patterns of shrimp in Chesapeake Bay, (2) relate relative abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
2
3
0
1
Order By: Relevance
“…The relationship between spawning biomass and shrimp in the Pamlico Sound was strongest for white shrimp where the spring CPUE of white shrimp captured in the SEAMAP survey on the North Carolina shelf was the most important variable explaining the estimated abundance of white shrimp in the Fall in the Pamlico Sound (Fig 8c). This same relationship has been observed in the Chesapeake Bay, where the SEAMAP CPUE of white shrimp is positively correlated with the CPUE for Virginia Institute of Marine Science (VIMS) trawl survey [70] and South Carolina's ACE basin [61], suggesting this relationship is not exclusive to North Carolina or local conditions. Similarly, researchers in the Chesapeake Bay found the relationship between indices of adult abundance and subsequent juvenile recruitment was strongest for white shrimp relative to brown and pink shrimp [70].…”
Section: Plos Onesupporting
confidence: 66%
See 2 more Smart Citations
“…The relationship between spawning biomass and shrimp in the Pamlico Sound was strongest for white shrimp where the spring CPUE of white shrimp captured in the SEAMAP survey on the North Carolina shelf was the most important variable explaining the estimated abundance of white shrimp in the Fall in the Pamlico Sound (Fig 8c). This same relationship has been observed in the Chesapeake Bay, where the SEAMAP CPUE of white shrimp is positively correlated with the CPUE for Virginia Institute of Marine Science (VIMS) trawl survey [70] and South Carolina's ACE basin [61], suggesting this relationship is not exclusive to North Carolina or local conditions. Similarly, researchers in the Chesapeake Bay found the relationship between indices of adult abundance and subsequent juvenile recruitment was strongest for white shrimp relative to brown and pink shrimp [70].…”
Section: Plos Onesupporting
confidence: 66%
“…This same relationship has been observed in the Chesapeake Bay, where the SEAMAP CPUE of white shrimp is positively correlated with the CPUE for Virginia Institute of Marine Science (VIMS) trawl survey [70] and South Carolina's ACE basin [61], suggesting this relationship is not exclusive to North Carolina or local conditions. Similarly, researchers in the Chesapeake Bay found the relationship between indices of adult abundance and subsequent juvenile recruitment was strongest for white shrimp relative to brown and pink shrimp [70]. In the present study we found the spring spawning biomass of white shrimp was highly correlated with winter water temperature, suggesting that although the spawner-recruit relationship was dominant for white shrimp, temperature was an underlying factor in that relationship.…”
Section: Plos Onesupporting
confidence: 66%
See 1 more Smart Citation
“…Se espera que la abundancia de especies subtropicales como el pinfish y el camarón blanco aumente en la Bahía de Chesapeake y en las lagunas costeras, mientras que las especies más templadas, como la almeja blanda y el camarón de arena, podrían disminuir 97,98 . En la Bahía de Chesapeake, se ha observado un aumento de la abundancia de camarón blanco 99 , que se relacionó con condiciones medioambientales favorables, incluido el aumento de las temperaturas. Las proyecciones de períodos invernales más cortos y temperaturas invernales más cálidas en la Bahía de Chesapeake sugieren que en 2100 los cangrejos azules crecerán más rápido y mejorarán su supervivencia durante el invierno, lo que aumenta la productividad de la población 100 .…”
Section: Cambios En La Distribución De Los Recursos Pesqueros En El O...unclassified
“…Hollebone, 2006 ; Shearman and Lentz, 2010 ). Among these biotic changes is the increased prevalence of a condition known as black gill (Fowler et al ., 2018 ; Swinford and Anderson, 2021 ; Tuckey et al ., 2021 ). This condition refers to the melanization of gill tissues that occurs as part of an immune response against irritants or pathogens (Vaseeharan and Ramasamy, 2003 ; Johnson et al ., 2011 ; Burnett and Burnett, 2015 ; Karthikeyan et al ., 2015 ; Frischer et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%